Effect of severity of depression and perceived social support on suicidal ideation among patients hospitalized with substance use disorder - Baziki Çetin, Sıdıka; Peker, İrem and Atılan Fedai, Ülker (Journal of Dependence, 2024)
Objective: The aim of this study was to investigate the effects of perceived social support and depression on suicidal ideation in inpatients receiving substance abuse disorder treatment. Method: A total of 110 inpatients in an Alcohol and Drug Treatment Center were included in the study. A sociodemographic and clinical information form, Beck Depression Inventory, Suicidal Ideation Scale, and Multidimensional Perceived Social Support Scale were administered to all patients. Results: No significant correlation was identified between total social support score and suicidal ideation, whereas a weak negative but statistically significant correlation was found between social support from family and suicidal ideation scores (r=-0.231; p=0.016). The mean value of suicidal ideation was 2.22 in the non-depressed groupand 10.13 in the severely depressed group. We also found thatpatients whowere exempted from military service and those who had attempted suicide before had statistically significantly higher scores on the suicidal ideation scale. Conclusion: In patients diagnosed with substance use disorder, various factors may increase the risk of suicidal behavior. In particular, patients with insufficient social support, depressive symptoms, unable to carry out their military service and those who have attempted suicide before should be closely followed for suicidal ideation.